THE INFLUENCE OF WORD ATTACK STRATEGY TOWARD THE STUDENTS READING COMPREHENSION ACHIEVEMENT OF THE SEVENTH GRADE STUDENTS AT SMP NEGERI 1 PRABUMULIH - Novitasari, Hesti; Saputri, Kurnia; Hartati, Sri; Saraswaty, Dwi Rara (English Community Journal, 2021)
This research entitled “The Influence Word Attack Strategy toward the Students Reading Comprehension Achievement of the Seventh Grade at SMP Negeri 1 Prabumulih”. The problem of this research “is there any influence to teach reading comprehension by using the word attack strategy of the seventh grade students at SMP Negeri 1 Prabumulih?” The objective of this research was to find out whether or not there is an influence to teach reading comprehension achievement of the seventh grade students at SMP Negeri 1 Prabumulih? The Population of the research was the seventh grade students at SMP Negeri 1 Prabumulih, with the sample were 34 students. The test consisted of 30 questions that were multiple-choice questions. The data were calculated through SPSS 22.0 Program. The result of data analysis showed that t-obtained was       -7.884, with the critical value 20.345, at the Null Hypothesis (Ho) was rejected, and Alternative Hypothesis (Ha) was accepted. It could be concluded that there was a significant influence of word attack strategy on the students’ reading comprehension. In this case, word attack strategy can develop students’ ability, especially for the Seventh Grade Students at SMP Negeri 1 Prabumulih.